Improving Posyandu Cadres knowledge through stunting education and training on sea fish–based MPASI and PMT preparation in Darungan Village - Ira Humairah; Patmawati Patmawati; Ema Qurnianingsih; Lina Lukitasari; St. Khaerunnisa; Fithriyah Cholifatul Ummah; Langgeng Agung Waskito; Citrawati Dyah Kencono Wungu; Imanta Alifia Oktavira; Novita Nur Ramadhani; Dede Sayyidatunnisa; Muhammad Hidayat; Gwenny Ichsan Prabowo (LPPM Universitas Syiah Kuala, 2026)
Background and Aim: Stunting remains a major public health problem that affects child growth and development. Community-based nutritional interventions utilizing local food resources are important strategies to support stunting prevention. This community service activity aimed to improve the knowledge and skills of Posyandu cadres regarding stunting prevention through education and training on the preparation of sea fish–based MPASI and PMT in Darungan Village. Methods: The program was conducted using educational counseling, practical training, and mentoring activities for Posyandu cadres. Participants received materials on stunting prevention, balanced nutrition, and practical demonstrations of preparing sea fish–based MPASI and PMT. Knowledge improvement was evaluated using pre-test and post-test assessments. Results: The results showed a significant increase in participants’ knowledge regarding stunting prevention and balanced nutrition, with a p-value of 0.025 (p < 0.05). In addition, participants demonstrated improved practical skills in preparing nutritious sea fish–based complementary and supplementary foods for children. Conclusion: Education and training using locally available sea fish as nutritional resources effectively improved Posyandu cadres’ knowledge and practical skills in stunting prevention. This program has the potential to support sustainable community-based nutrition interventions and contribute to achieving Sustainable Development Goal (SDG) 3, namely Good Health and Well-being.